Color Field Test Charts Vs HVFA In Detection Visual Field Defect Chronic Primary Glaucoma - Tanoko, Ivana; Winarto, Winarto; Nugroho, Trilaksana; Prihatningtias, Riski; Rahmi, Fifin L (Majalah Oftalmologi Indonesia, 2022)
Introduction: Glaucoma is syndrome consist of glaucomatous optic neuropathy, destruction of retinal nerve fiber layer, and typical visual field defects. Color field test charts (CFTC) is a simple and generous instrument used to detect central and paracentral scotoma in neuro-ophthalmology patient. Diagnostic study will perform in this research to compare visual field defects, detecting in chronic primary glaucoma patient between CFTC and HVFA SITA 10-2 as gold standard. Methods: Seventy two eyes from 50 patients with chronic primary glaucoma were examined visual acuity, funduscopy, color blindness, HVFA SITA 10-2 and CFTC. The results CFTC and HVFA were read by 2 ophthalmologists, and kappa agreement was done. Analysis was done to get sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), accuracy, positive and negative likelihood ratio (LR). Result: The sensitivity of CFTC was 87.93%, specificity 85.71%, PPV 96.22%, NPV 63.16%, accuracy 87.5%, positive LR 6.15 and negative LR 0.14 in detecting visual field defect chronic primary glaucoma patient compared to HVFA SITA 10-2. Area Under Curve (AUC) in this research was 0.86 (95% CI 0.751-0.985, p<0.001). Sensitivity, PPV, and accuracy was higher in MD >-12dB compared to <-12dB. There was strong correlation between it in location of defect (Cramer’s correlation; V=0.679, p<0.001), although the large of visual field defect was significantly different between 2 instruments (p<0.05). Conclusion: Color field test charts is comparable to HVFA SITA 10-2 in detecting visual field defect chronic primary glaucoma moderate and advance stage.